Suicídio : dos modelos teóricos à proposição de um manual informativo para profissionais de saúde - Ligório, Isadora Silveira (2021)
Suicide is characterized by an intense psychological pain. In addition to individual impacts, friends, family and society are also affected. Despite being considered a worldwide public health problem, the stigma associated with this type of psychological suffering is still present. The lack of knowledge and the taboo about the phenomenon can influence the provision of health care to people who exhibit this behavior. Informing and training health professionals about suicide is a way of destigmatizing it and improving care for these cases. This dissertation is divided into two sections, which include two studies and a technicalscientific manual. The theoretical section consists of a non-systematic review of empirical studies on recent theoretical models and constantly cited in the literature on suicide. This first production helped to understand the manifestation of suicidal behavior and provided important support for the construction of a technical manual for health professionals on intervention in suicidal ideation and attempted suicide. The material is structured in four chapters and addresses the following themes: suicide, associated behaviors, epidemiology, stigma and impacts; factors associated with the phenomenon, theoretical models and warning signs; attendance, evaluation, referral and notification; and self-care of the professional. The empirical section consists of a methodological study of development and evaluation of the referred technical-scientific manual. In order to guarantee technical quality, feasibility and comprehensiveness, the manual was evaluated by four expert judges and 14 health professionals. An online questionnaire was conducted with multiple choice questions and open questions to analyze criteria for clarity and pertinence about the content of the manual. In general, the evaluations were positive and the changes pointed out were accepted. The material demonstrated good adherence by professionals, in which the accessibility of information and the need for self-care in professional practice were positively highlighted in the assessment. The elaboration of materials on suicide is a possibility to guarantee health professionals access to scientific information and to instrumentalize them for the adequate care to these cases. The subsequent evaluation is important to improve and adapt the knowledge to the daily reality of these professionals.